Efeito do estufim e da aplicação de AIB na produtividade efetiva de mudas clonais de Corymbia torelliana × Corymbia citriodora - Lima, Marllos Santos de (2022)
The Brazilian Forest sector contributes worldwide to the supply of wood, cellulose and paper, among other by-products originating from planted forests and, for the most part, certified by international organizations that guarantee the sustainable management of this resource. The country achieved this position at a global level due to the high productivity of planted forests, due to the edaphoclimatic conditions found in the Brazilian territory and the development of highly productive genetic materials. Currently, companies in the steel and pulp and paper sectors have shown interest in clones of pure and hybrid species of the genus Corymbia, due to the high density of wood, resistance to pests and diseases and to abiotic factors such as water stress. In addition, the genus becomes an alternative for the possible stagnation of productivity in planted forests. However, genetic materials of the genus have been classified as difficult to propagate vegetatively, as they present rooting rates below 70%. In view of this scenario, the present research aimed to evaluate the effect of the application of different doses of IBA together with the use of the mini-tunnel during the production of shoots and during the rooting of mini-cuttings on the variable survival, rooting and morphological quality of the cutlings at over three seasons. The research was carried out in a subtropical climate region (Barra do Ribeiro, RS) over three seasons (winter, spring and summer) in a factorial scheme (2 x 2 x 4) with split-split plots, the main plot being composed of two shoot production environments (mini-garden with and without a mini-tunnel), the split-plot by two rooting environments (greenhouse with and without a mini-tinnel) and the split-split plot by four concentrations of indole-3-butyric acid (AIB) (0, 1,500, 3,000 and 4,500 mg L-1). The results obtained in the research showed that the clone studied presents greater effective productivity during the winter, to the detriment of the greater adventitious rooting of the mini-cuttings. In addition, it was found that the use of the mini-tunnels in the clonal mini-garden enhances the rooting of mini-cuttings. These results are mainly explained by the higher turgidity of the mini-stumps and lower physiological stress during the collection of shoots. Another important result obtained in the research refers to the use of IBA which do not increase the survival of mini-cuttings at 30 days after propagation and the morphological quality of cutlings at 120 days. In view of this, it is concluded that the production of cutlings of the hybrid C. torelliana × C. citriodora should be prioritized during the cold periods of the year (winter) and the mini-tunnel in the mini-garden should be carried out in all seasons of the year. In addition, we concluded that to produce Corymbia cutlings it is not necessary to use IBA.